Understanding dental caries as a non-communicable and behavioral disease: Management implications - Giacaman, Rodrigo A.; Fernández, Constanza E.; Muñoz-Sandoval, Cecilia; León, Soraya; García-Manríquez, Natalia; Echeverría, Constanza; Valdés, Sebastián; Castro, Ramiro J.; Gambetta-Tessini, Karla (Frontiers in Oral Health, 2022)
New paradigms in caries conceptualization have emerged during the last decades, leading to intense debate and discussion on how to approach the disease, both from a preventive and a therapeutic perspective. Among many new ideas, research discoveries and technologies, one major concept can be highlighted that created a deep frontier between the old and the new paradigm in caries conceptualization; the non-communicable nature of the disease, firmly associated with behaviors and lifestyles. This article synthetizes the conceptual construction of dental caries as a non-communicable disease (NCD) based on the current evidence and discusses the appropriate management of the disease in this context. Dental caries has shifted from being considered transmissible and infectious to an ecological and non-communicable disease. Environmental factors such as frequent sugars intake, disrupt the symbiosis of the dental biofilm leading to a dysbiosis, which favors caries lesion initiation and progression. As an NCD, dental caries shares characteristics with other NCDs such as cardiovascular and chronic respiratory diseases, cancer and diabetes, including long duration and slow progression, not being transmissible from person-to-person, being strongly related to modifiable behavioral risk factors, and affecting preferentially disadvantaged populations with a strong inequality gradient. Given the high prevalence of dental caries disease, and its consequences on people’s health and quality of life, a recognizable conceptual view of caries as a NCD is required to target an effective management. Current understanding of dental caries supports prevention through acting on the modifiable risk factors (behaviors) and involves management based on an interdisciplinary approach. Communicating these modern concepts among researchers, clinicians and policymakers is needed to decrease the global high burden of the disease.